Petrography, mineral chemistry and geothermobarometry of retroeclogite of araxá group from varginha shear zone region, southwest of minas gerais state - Leme, Thaís Güitzlaf [UNESP]; Navarro, Guillermo Rafael Beltran [UNESP]; Zanardo, Antenor [UNESP]; Montibeller, Cibele Carolina [UNESP] (My University, 2020)
The study area is located in the southwest of Minas Gerais state, north of the Guaxupé city and in the vicinity of the Santa Cruz do Prata district (Guaranésia municipality), a region affected by the Varginha Shear Zone. It is constituted of lithotypes attributed to the Araxá Group, placed in a suture zone of crustal blocks, and amalgamated during the Brazilian orogenesis in Neoproterozoic (Alterosa Suture Zone). In this region, the Araxá Group is composed of pelitic to psamo-pelitic metasediments with orthogneisses, metamafic and metaultramafic rocks intercalations. Interleaved with these lithotypes, it was described high pressure metamafic rocks occurrences with symplectic and coronitic textures which were interpreted as retroeclogites. In this paper are presented petrographic, mineral chemistry and geothermobarometric data obtained in retroeclogite. The geothermobarometry results by trace elements (Zr-in-rutile and Ti-in-quartz) indicate older metamorphic rebalancing conditions in eclogite facies, with temperature of 763°C and pressure of 14.4 kbar. The rebalancing conditions in upper amphibolite facies, calculated by the THERMOCALC software, are 12.5 ±0.8 kbar and 799 ±37 °C. The textural and mineralogical data, combined with geothermobarometric data, suggest a clockwise P-T-t path associated to near isothermal decompression. The results are compatible with continental collision zones with crustal thickening.
Petrografia, química mineral e geotermobarometria de retroeclogito no grupo araxá na região da zona de cisalhamento varginha, sudoeste de minas gerais
Keywords: Alterosa suture zone; Eclogite facies; Southern brasília belt; Varginha shear zone